A comparative study to assess the accuracy of the SRK T and HOFFER Q formulas in the intraocular lens calculation of long eyes undergoing phacoemulsification with posterior chamber intraocular lens in a tertiary care center - H Mohan Kumar; N Apoorva; Shreya; B Rachana; Sana Rasheed; Jyotsana Soni (Journal of Clinical Ophthalmology and Research, 2023)
Aims and Objectives: The aim is to compare the accuracy of the SRK T and HOFFER Q formulas in intraocular lens (IOL) power calculation in long eyes by noting the postoperative visual outcome. Introduction: Senile cataract is a leading cause of blindness in India. Cataracts are managed by cataract extraction with implantation IOL. Before surgery, IOL power is calculated by biometry. IOL power calculation is the main key to obtaining a good refractive outcome after cataract surgery. Materials and Methods: A hospital-based study was conducted prospectively to evaluate IOL power using SRK T and HOFFER Q formulae in patients undergoing phacoemulsification with posterior chamber intraocular lens in long eyes over a period of 18 months. Thirty patients were studied based on inclusion criteria. A detailed clinical examination, pre- and postoperative visual acuity, anterior chamber depth (ACD), and refraction were done on day 30 postsurgery. Results: The study included 30 cases with 15 patients in either group, of which 63% were male and 37% were female; 95% of the patients were aged above 50 years; the maximum number of patients in either group had an axial length in the range of 24.5–25 mm; the maximum preoperative ACD was between 3 and 4.5 mm and the maximum postoperative ACD was between 4 and 4.5 mm in both groups; 40% of the patients in either group had 6/6 vision; spherical refractive error postoperative was seen in 73% in the SRK T group and 68% in the HOFFER Q group; and cylindrical refractive error was seen in 27% in SRK T group and 32% in HOFFER Q group. Conclusion: Either formula can be used for IOL power calculation in eyes up to 26.5 mm, as not much difference in postoperative refractive error was observed. Both formulas had a lesser degree of spherical error and an equally good visual outcome postoperatively. Careful biometry is important to prevent postoperative surprises.